2006
DOI: 10.1016/j.jml.2005.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Heavy NP shift is the parser’s last resort: Evidence from eye movements☆

Abstract: Two eye movement experiments explored the roles of verbal subcategorization possibilities and transitivity biases in the processing of heavy NP shift sentences in which the verb's direct object appears to the right of a post-verbal phrase. In Experiment 1, participants read sentences in which a prepositional phrase immediately followed the verb, which was either obligatorily transitive or had a high transitivity bias (e.g., Jack praised/watched from the stands his daughter's attempt to shoot a basket). Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…These results are in line with a range of observations from several languages suggesting that verb transitivity information crucially determines the processing of arguments encountered in post-verbal positions (e.g. Ferreira and McClure, 1997;Pablos, 2006;Staub et al, 2006;Staub, 2007). However, Pickering et al (2000) provided compelling evidence for a general direct object preference in the processing of NP-S ambiguities, by demonstrating effects of direct object plausibility in the ambiguous region even for verbs that were biased towards an intransitive reading.…”
Section: The Limitations Of Minimality Propersupporting
confidence: 87%
“…These results are in line with a range of observations from several languages suggesting that verb transitivity information crucially determines the processing of arguments encountered in post-verbal positions (e.g. Ferreira and McClure, 1997;Pablos, 2006;Staub et al, 2006;Staub, 2007). However, Pickering et al (2000) provided compelling evidence for a general direct object preference in the processing of NP-S ambiguities, by demonstrating effects of direct object plausibility in the ambiguous region even for verbs that were biased towards an intransitive reading.…”
Section: The Limitations Of Minimality Propersupporting
confidence: 87%
“…In production, Stallings et al (1998) found that heavy NP shift was lower with verbs which had high expectations for a noun phrase complement compared to more promiscuous verbs. In comprehension, Staub, Clifton, and Frazier (2006) found that pairings of verbs that were biased towards noun phrase complements (transitive-biased condition) with post-verbal adjuncts or prepositional phrases that signaled heavy NP shift did not lead to immediate slowing due to reanalysis. Therefore, comprehenders were not biased to expect heavy NP shift in these ambiguous situations and verbs which might provide clear signals for heavy NP shift in language learning did not appear more in shifted structures.…”
Section: Word Ordering Phenomena In English and Japanesementioning
confidence: 99%
“…Although earlier work documenting these effects focused primarily on expectations at the lexical level, more recent work has provided evidence for expectations at the level of syntactic constituency on the basis of grammatical analysis of prior linguistic content (Lau, Stroud, Plesch & Phillips, 2006;Staub, Clifton & Frazier, 2006;Jaeger, Fedorenko, Hofmeister & Gibson, 2008;Levy, Fedorenko, Breen & Gibson, 2012).…”
Section: Introductionmentioning
confidence: 99%